Comunicação pública e rastros digitais: uma estratégia para fortalecer novas políticas públicas na Assembleia Legislativa da Paraíba - Macêdo, Caio Moura de Arroxelas (2024)
The present work proposes the construction of an artifact – a communication strategy – in the Legislative Assembly of Paraíba. This strategy enables content producers to develop a communication flow that involves monitoring the most recurring themes, organizational communication, information curation, metrics analysis and, finally, the systematization of these elements in a report. . In this way, digital traces present themselves as a new format of participation and with the possibility of being implemented in public policies. The methodology used was Desigin Science Research and the bibliographical tangle contextualized concepts from different fields of research towards involving content production as an instrument to supplement parliamentary activities and constitute a social component. The communication strategy was conducted and tested through a methodological path that supported scientific rigor in 7 steps: reasons for carrying out research, research objectives, scientific methods, research methods, working method, data collection and analysis techniques , and reliable results.